Pengaruh Return on Assets, Sentimen Pasar, Dan Kinerja Kompetitor Terhadap Harga Saham (Pada Perusahaan Sektor Perbankan Yang Terdaftar Di Bursa Efek Indonesia Tahun 2018-2023) - Yani, Tiara Sulis Tri; Ridwan, Ridwan (Jurnal Ilmu Sosial, Manajemen, Akuntansi dan Bisnis, 2024)
This research was conducted to determine the influence of return on assets, market sentiment, and competitor performance on share prices in banking sector companies listed on the Indonesia Stock Exchange during the 2018-2023 period. The method used in this research is quantitative with a verification approach. The research sample consisted of 5 banking companies with a research period of 6 years, selected using a purposive sampling technique, so that the total amount of data studied was 30 data. Multiple linear regression analysis is used to determine the influence of the independent variable on the dependent variable, either partially or simultaneously. The results of data analysis show that, both partially and simultaneously, return on assets, market sentiment and competitor performance influence share prices.